Analisis Postur Kerja dengan Pendekatan Ergonomi Pada Home Industry Snack dan Katering “X” di Kota Semarang - Indah Permatasari; Bayu Yoni Setyo Nugroho; Izzatul Alifah Sifai (Journal Occupational Health Hygiene and Safety, 2023)
ABSTRACTSemarang is a region known for its culinary diversity and cultural heritage. The number of tourists visiting is proportional to the number of culinary and tourism industries. The city of Semarang continues to strive to increase the participation of small and medium enterprises in order to advance the region and prosper the community. The mushrooming of small and medium industries in Semarang is still not directly proportional to efforts to protect occupational safety and health for its workers. Even though work safety and health efforts are mandatory things that must be pursued both for formal and informal industries. The research aims to determine the level of risk and improve work posture with an ergonomic approach in the form of a Rapid Upper Limb Assessment (RULA) worksheet and observations in the snack and catering industry. Food processing and packaging workers have a high level of risk of experiencing muscle and bone pain because most of their work activities are sitting. The measurement results for workers in industry X show a score of 4 in the dough making section, a score of 3 in the processing section 1, a score of 4 in the processing section 2. A score of 3 in the packaging section 1, and finally a score of 4 in packaging 2. The results prove that there is no tension muscles in workers but there is discomfort in work positions that are affected by work facilities. Corrective and preventive efforts need to be pursued so that workers are able to work productively and in the future there will be no occupational diseases.